The Influence Of Digital Marketing And VAT (Value Added Tax) Literacy On Consumer Purchasing Behavior - Lingga, Shonia Mehangga; Sitompul, Grace Orlyn; Purba, Heddry (Moneter: Jurnal Keuangan dan Perbankan, 2024)
This study aimed to examine the impact of digital marketing and VAT (Value Added Tax) literacy on consumer purchasing behavior. It investigates how marketing through digital media, along with VAT literacy, can affect respondents as consumers across both online and offline platforms. The research employs a quantitative approach, utilizing primary data collected through questionnaires and multiple linear regression techniques. The population consists of 387 students from “Universitas Advent Indonesia,” who graduated in 2023, with a sample of 151 students from the economics faculty. The sampling method used is probability sampling, resulting in 82 respondents. The independent variables are digital marketing and VAT (Value Added Tax) literacy, while the dependent variable is consumer purchasing behavior. This study utilizes SPSS 27 software. The findings indicate that digital marketing and VAT literacy, when considered together, influence consumer purchasing behavior. Additionally, the results of the study shows that effective digital marketing strategies can strengthen consumer relationships and enhance loyalty, making them essential in today’s digital age. However, VAT literacy has little impact on purchasing behavior since the surveyed respondents already have high VAT literacy.